Digital Banking : A Meta-Analysis Approach - Sharma, Suneet; Sharma, Ritu; Kayal, Ghadeer; Kaur, Jaspreet (Indian Journal of Marketing, 2022)
This research paper attempted to study the behavioral intention adoption of prominent digital banking channels, such as mobile banking and wallets and online and telephone banking, in an international scenario. The behavioral intention adoption of mobile banking was studied through seven bivariate relationships: perceived usefulness, perceived ease of use, facilitating conditions, perceived security, cost, self-efficacy, and innovativeness in a global context, which have had a profound impact on the desire of people to adopt digital banking channels. The seven bivariate relationships were analyzed through a meta-analysis approach in a universal framework. The main findings were that location is a major contributor to heterogeneity in a comprehensive global framework. The main managerial implications of the paper are that the universal adoption of digital banking adoption is being significantly affected by location, and global strategists should, therefore, keep this constraint in mind while framing international policies and launching new digital products. Such products must appeal to the location to be successful. An important social link that the current research highlighted was that location has vital linkages with other social factors such as religion, caste, race, color, income, gender, education, family size, buying habits, and wealth, which need to be explored in detail for a better examination of the successful adoption of digital banking channels.